Hybrid capture II and PapilloCheck® tests for detection of anal high-risk human papillomavirus - Maia, Livia Bravo (2014)
Introduction: This study evaluated the level of concordance between hybrid capture II (HCII) and PapilloCheck® for the detection of high-risk human papillomavirus (HPV) in anal samples. Methods: Anal cell samples collected from 42 human immunodeficiency virus (HIV)+ patients were analyzed. Results: Considering only the 13 high-risk HPV types that are detectable by both tests, HCII was positive for 52.3% of the samples, and PapilloCheck® was positive for 52.3%. The level of concordance was 80.9% (Kappa = 0.61). Conclusions: Good concordance was observed between the tests for the detection of high-risk HPV.